Friendships in Online Peer-To-Peer Lending: Pipes, Prisms, and Relational Herding1 - Liu, De; Brass, Daniel J.; Lu, Yong; Chen, Dongyu (MIS Quarterly, 2015)
This paper investigates how friendship relationships act as pipes, prisms, and herding signals in a large online, peer-to-peer (P2P) lending site. By analyzing decisions of lenders, we find that friends of the borrower, especially close offline friends, act as financial pipes by lending money to the borrower. On the other hand, the prism effect of friends’ endorsements via bidding on a loan negatively affects subsequent bids by third parties. However, when offline friends of a potential lender, especially close friends, place a bid, a relational herding effect occurs as potential lenders are likely to follow their offline friends with a bid.